TOWARDS THE INFORMATION SOCIETY: THE BIRTH AND DEVELOPMENT OF THE NEW RECORDS CULTURE - ROMAN, WANDA KRYSTYNA (Knygotyra, 2012)
Though the ages (Antiquity, Middle Ages, Modernity and the Present), humanity developed successive cultural systems: oral, written, print, industrial, and electronic. The records culture is a component, or manifestation, of nearly every type of culture. Records culture should be defined as the overall body of motivations, attitudes and behaviours of the producers and users of records that occur during the planned and effective creation, collection, retention, processing, and sharing.
Keywords: information society; information culture; records culture; record-keeping